Psychometric Validation of the Scale of Individual Cultural Values (CVSCALE) in Indian Context (Private and Public Leaders in Indian Organizations) - Dhingra, Deepika; Srivastava, Sanjay; Srivastava, Nandini (Journal of Ecohumanism, 2024)
Existing measures of cultural orientations at the organizational level rely heavily on Hofstede's national cultural dimension scores, which overlook individual variability within countries. The Individual Cultural Values Scale (CVSCALE) measures individual orientations directly. This study aimed to investigate the factor structure and reliability of the CVSCALE for use with Indian corporate leaders. Data was collected from 321 Indian organizational leaders using the 26-item CVSCALE. Factor structure and psychometric properties were examined through exploratory factor analysis and reliability analysis. A five-factor structure consistent with CVSCALE dimensions emerged. Reliability coefficients exceeded acceptable thresholds (α = 0.901; split-half = 0.794). Dimension scores ranged from low to high, contrasting some of Hofstede's national Indian scores. Results support the CVSCALE as a reliable, valid tool for directly assessing cultural orientations at the individual level within Indian organizations. While uncertainty avoidance was high, other dimensions varied individually. This highlights that culture is complex, with diversity existing below the national level. The CVSCALE enables rich cultural analysis beyond solely examining nationality